2004
DOI: 10.1111/j.1532-950x.2004.04024.x
|View full text |Cite
|
Sign up to set email alerts
|

Femur Fractures Associated with Canine Total Hip Replacement

Abstract: Femur fractures that occur after THR should be repaired using plate and screw fixation augmented with cerclage wire when needed. Forces on fissures should be neutralized to prevent propagation and fracture. Owners of high-risk patients (old dogs with osteopathies or previous hip surgery) should be counseled before THR. The prognosis is excellent when fractures are treated correctly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
127
2
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(144 citation statements)
references
References 13 publications
13
127
2
2
Order By: Relevance
“…The improper length of stem can lead to loosening or displacement of the cement plug into distal medullary canal (Noble et al, 1988). The postoperative fracture risk also may increase with misplacement of the tip of stem because femoral fractures associated THA are mostly occurred near the stem tip related incorrect loading of this region (Liska, 2004). The isthmus was placed between 42.72% and 45.36 % below the top of dog femora in present study.…”
Section: Discussionmentioning
confidence: 70%
“…The improper length of stem can lead to loosening or displacement of the cement plug into distal medullary canal (Noble et al, 1988). The postoperative fracture risk also may increase with misplacement of the tip of stem because femoral fractures associated THA are mostly occurred near the stem tip related incorrect loading of this region (Liska, 2004). The isthmus was placed between 42.72% and 45.36 % below the top of dog femora in present study.…”
Section: Discussionmentioning
confidence: 70%
“…These fissures were due to the proximal diameter stem incompatibility to the proximal diameter of the femur; canine latin prostheses even cemented have a larger proximal stem diameter than other commercial models leading to overpreparation of the femur canal by the surgeon, thus leading to microfissure formation. Other studies (Olmstead et al, 1983;Massat and Vasseur, 1994;Liska, 2004) report observation of the same fracture localizations and postoperative time of presentation. In this study, incidence of fractures and fissures were presented in either cemented or cementless systems with the same rate, which is in opposition to the report from Montgomery et al (1992).…”
Section: Discussionmentioning
confidence: 89%
“…It might be useful in resolution and revision cases of total hip prosthesis femoral fracture (Liska, 2004), in such cases where it is not possible to position a plate with bicortical screw insertion because of the presence of the stem inside the canal impeding the insertion of the screws (Murphy et al, 1997;Liska, 2004). This study opened the possibility for using the locking prosthesis in cases which processes of osseous resorption, aseptic loosening and fractures are the main issues.…”
Section: Discussionmentioning
confidence: 99%
“…This reflection was investigated in two observational retrospective studies: Liska (2004) and Ganz et al (2010). Both studies reported that elderly dogs undergoing THR may be at an increased risk of femoral fractures.…”
Section: Appraisal Application and Reflectionmentioning
confidence: 99%
“…Both studies reported that elderly dogs undergoing THR may be at an increased risk of femoral fractures. According to Liska (2004) old dogs with osteopathies, previous hip surgery and iatrogenic fissures created during reaming are predisposing factors for femur fracture after THR. The overall incidence of femur fracture after THR was 2.9%.…”
Section: Appraisal Application and Reflectionmentioning
confidence: 99%